URBANIZATION PROCESSES ON UKRAINIAN LANDS AS PART OF THE RUSSIAN EMPIRE IN THE LATE 19TH AND EARLY 20TH CENTURY (Південний архів (історичні науки), 2023)
Purpose. The article is devoted to the analysis of urbanization processes that took place on Ukrainian lands as part of the Russian Empire at the end of the 19th and the beginning of the 20th centuries. Particular attention is focused on industrialization as the main factor of city formation and demographic changes. Methods. The research methodology is based on the principles of historicism, systematicity, scientificity, objectivity and interdisciplinarity. Both general scientific methods (analysis, synthesis) and historical ones (historiographical and comparative historical analysis, historical-genetic, historical-systemic) were used. Among the interdisciplinary methods, statistical and mathematical methods (tabular and time series analysis) have found application. Results. The results of the study made it possible to conclude that the urbanization processes were a logical outcome of the socio-economic development of the territory of Dnipro Ukraine in the late 19th and early 20th centuries, which testified to the fundamental processes that took place in the social structure of the population. It was revealed that their course in time and space was influenced by various economic, demographic and social factors. Emphasis is placed on the fact that in terms of the pace of urbanization, Dnipro Ukraine lagged far behind the leading states: while the countries of Western Europe were at the secondary and tertiary stages of the urbanization process, it was only at the primary one. Economic and social aspects of industrial modernization were analyzed. The highest level of urbanization was observed in the southern provinces, which, in addition, had the highest indicators of the migration potential necessary for the development of urbanization processes. Conclusions. On the basis of the study, it can be concluded that urbanization in the territory of Ukraine controlled by Russia was not uniform, had an unfinished, one-sided character, which was the result of its formation as a by-product of industrialization. It was established that the degree of development of urbanization trends was insufficient to state the serious successes of the urbanization process. Further research into the history of urbanization processes on Ukrainian lands within the Russian Empire of the specified period has great prospects. This concerns, first of all, not only quantitative, but also qualitative indicators of urbanization, in particular, such as the ethnic composition of urban residents, social mobility of the urban population, urban culture, and the quality of the urban environment.
Keywords: Ukraine controlled by Russia, provinces, cities, urban population, industrialization, migration, demographic process